Modernism at the University: New Elocution, New Criticism, and New Poetry. (April 2017) - Somers, Matthias
Abstract : As models of academic literary study, it would appear that elocution and New Criticism could not be further apart. While elocution (the theory and art of reading aloud) supposedly belonged to a pre‐modernist, genteel type of criticism derived from traditional rhetoric, New Criticism is considered the quintessentially modern, serious, and professional type of criticism. Yet, a close look at the elocutionary tradition by means of two concise case studies – those of turn‐of‐the‐century elocutionists Samuel Silas Curry and Solomon Henry Clark – shows more similarities than differences. It is therefore argued that the demise of elocution as a mode of literary study was not caused by the revolutionary action of the New Critics, but by impersonal, institutional factors that played into the hands of New Criticism. The focus on elocution helps to raise the right questions about the complex relation between modernism and rhetoric, and about the delineation of a modernist canon by the New Critics, who supposedly adopted the anti‐rhetorical aesthetic dicta of high modernism. Yet, this article argues that the exclusion of the American "New Poets" from the modernist canon can only be explained by the same pressure of academic professionalization that had advantaged New Criticism in academia.